2017
DOI: 10.1002/fam.2498
|View full text |Cite
|
Sign up to set email alerts
|

A method to assess downward flame spread and dripping characteristics of fire‐retardant polymer composites

Abstract: Summary A method is described to assess the flame retardancy of polyethylene composites by measuring both their downward flame spread rates as well as their combined melting and dripping rates on rectangular rods, ignited at their top. The composite materials were produced by mixing pulverized polymer with organic additives of differing particle sizes, shapes, and mass fractions. The resulting mix was melted in a mold, and then it was solidified into rods. The additives were carbonaceous solids with particle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Wen et al investigated the downward flame spread of low‐density polyethylene containing different micron and nano‐sized particles, including carbon black, soot particulate, multi‐wall carbon nanotube, bituminous coals and calcium‐based compounds. From the mass loss and change in sample height, the melting and dripping rates were quantified.…”
Section: Existing Experimental Studies On Melting and Dripping Behavimentioning
confidence: 99%
“…Wen et al investigated the downward flame spread of low‐density polyethylene containing different micron and nano‐sized particles, including carbon black, soot particulate, multi‐wall carbon nanotube, bituminous coals and calcium‐based compounds. From the mass loss and change in sample height, the melting and dripping rates were quantified.…”
Section: Existing Experimental Studies On Melting and Dripping Behavimentioning
confidence: 99%
“…Kim et al [24] simulated the melting dripping behaviors of polypropylene (PP) under external radiation and simplified many influencing factors in the simulation process. Additionally, Wen et al [25] simulated the melting dripping of flame retardant polyethylene (PE); the results showed that the carbon particle additives could effectively reduce the dripping rate. These previous studies validate that the present study is meaningful to some extent for the safety evaluation of polymers.…”
Section: Introductionmentioning
confidence: 99%